2022
DOI: 10.1111/apa.16410
|View full text |Cite
|
Sign up to set email alerts
|

Development and an initial validation of the Responses to Illness Severity Quantification (RISQ) score for severely malnourished children

Abstract: Aim:To develop and perform an initial validation of a score to measure the severity of illness in hospitalised children with severe acute malnutrition (SAM).Methods: A prospective study enrolled SAM children aged 6-59 months hospitalised in Borno State, Nigeria. Candidate items associated with inpatient mortality were combined and evaluated as candidate scores. Clinical and statistical methods were used to identify a preferred score. Results:The 513 children enrolled had a mean age of 15.6 months of whom 48 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This tool aims to identify which children among those admitted to a Nigerian hospital with severe acute malnutrition that face a high risk of mortality. 1 The early detection of patients who are at risk of deteriorating is sensible and can assist health care professionals to prioritise patients. This is particularly important in resource-limited settings that manage high numbers of patients with limited resources and staff.…”
Section: Paediatric Early Warning Systems In Low-income Settings-putt...mentioning
confidence: 99%
See 2 more Smart Citations
“…This tool aims to identify which children among those admitted to a Nigerian hospital with severe acute malnutrition that face a high risk of mortality. 1 The early detection of patients who are at risk of deteriorating is sensible and can assist health care professionals to prioritise patients. This is particularly important in resource-limited settings that manage high numbers of patients with limited resources and staff.…”
Section: Paediatric Early Warning Systems In Low-income Settings-putt...mentioning
confidence: 99%
“…Dale et al state that RISQ score only represents one part of the RISQ system that the authors are developing. 1 The full package will be similar to the Bedside PEWS system, as it will include recommendations for care that are matched to local resources and integrated throughout the spectrum of care. This will be an interesting | 1659 EDITORIAL continuation of present study and will allow us to evaluate the true clinical value of the RISQ scoring system.…”
Section: Paediatric Early Warning Systems In Low-income Settings-putt...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Responses to Illness Severity Quantification scoring tool aims to identify which children admitted to hospital with severe acute malnutrition face the highest risk of mortality. Dahl et al evaluated the use of the tool in a Nigerian hospital and concluded that it identified high‐risk malnourished children on admission and during their hospital stay 2 . The tool may help healthcare professionals to prioritise patients and potentially improve survival.…”
Section: Paediatric Early Warning System For High‐risk Malnutrition I...mentioning
confidence: 99%
“…highest risk of mortality. Dahl et al evaluated the use of the tool in a Nigerian hos-pital and concluded that it identified high-risk malnourished children on admission and during their hospital stay 2. The tool may help healthcare professionals to prioritise patients and potentially improve survival.…”
mentioning
confidence: 99%